Uma avaliação dos padrões de caça do Estado de São Paulo - Azevedo, Olivaldi Alves Borges (2018)
Hunting is not a reserved theme for modern times, but, nowadays, the concern about your effects in the manifold wildlife has propelled new researches and review of the ongoing. From a legal point of view, there are five modes that set hunting: hunt, pursuit, catch, kill and use. Are called hunting acts, because they are executed to the detriment of the wild animals in their habitats. This work evaluated the hunting acts in the period between the years 2006 to 2015, in the São Paulo State, reported in official documents dispatched by the paulista Environmental Military Police. Counts 1.913 police records or occurrences, that transgressor (hunters) were accountable administratively, had their equipment used in hunting seized, as well as the dead animals of illegal practice. The geoprocessing of the occurrences allows to be verified that in all regions of the State there was hunting. In the evaluated period, in 74.6% of the municipalities there are records of occurrences in detriment of the wild fauna; of the 645 municipalities, 481 mark at least one hunting act. Using wild specimens is the most frequent hunting, which is expressed in the use of a wild specimen (popularly recognized by flame) to attract another of the same species. The species belonging to the Order of the Passeriformes are the most hunted in the State, frequent in 52,38% (n = 1,002) of all police occurrences. Of the ten most hunted species, seven are of the order of the Passeriformes. When considered only the police records with frequency of birds (n = 1,002), three species are present in 45.3% (n = 866) of them, Sicalis flaveola (canário-da-terra), Sporophila caerulescens (coleirinho-papa-capim) and Saltator similis (trinca-ferro). The number of occurrences involving the Passeriformes leads to the conclusion that they are targets of domestic traffic (State), mainly of the mentioned species. Rodentia, Cingulata and Squamata are the other main objects orders of the acts of hunting, whose species are hunting. Police incidents involving hunting include 391, of which 303 are frequented by the three orders placed, that is, in 77.5% of hunting activities were present. The specie Hidrochoerus hydrochaeris (capybara) of the order Rodentia, is the champion of the hunting occurrences (n = 173). The most frequent representative of Cingulata is Dasypus novemcinctus (tatu-galinha) (n = 88) and, from Squamata Tupinambis Teguixin (teiú) (n = 30) is the most popular hunting animal by hunters. Game hunting was reasonably specialized. With a certain frequency, for its engendration were used equipment or special or typical instruments, revealing itself in a certain selective way. The evaluation of these and other patterns of the São Paulo hunting made it possible to study the motifs of the hunting acts, which are embodied in hunting modalities. The modalities evaluated were those of subsistence and necessity, amateur and recreational and control. In the State of São Paulo, it was patented mainly recreational hunting that carried out by the simple pleasure or delight of the hunter. This modality appears as an end in itself, developed to the shred of any rule. The hunter uses the equipment that suits him best and does so in the places and periods he has listed, without any limitations or restrictions. Although human consumption is the goal of hunting, the mode of subsistence hunting as a standard established in the State of São Paulo was not attested. These and other analyzes promoted the making of the Charter of the Paulista Hunt, product of this work.